Heating of the cathode with a conical tip by atmospheric-pressure arc plasma. Issue 5 (11th July 2019) - Liao, Meng-Ran; Chen, Tang; Lv, Wei-Jian
Abstract : Purpose: In this study, the authors performed a numerical investigation on the heating of a hot cathode with a conical tip by atmospheric arc, taking into account of the two temperature sheath effect for the first time. Design/methodology/approach: The Schottky effect at cathode surface is considered, which is based on the analytic solution of a one-dimensional sheath model. The unified model allows one to predict the cathode-plasma heat transfer. Findings: The total heat flux to cathode surface is smaller than its components' heat flux due to electron back diffusion is as large as that due to ion flux with the increase of cathode length the total heat transported to the cathode body has an obvious decrease. Originality/value: It is found that two kinds of solution exist for the cathode with a 140° conical tip; however, only one stable solution exists when the conical angle is reduced to 130°.